THE USE OF TIKTOK APPLICATION: THE IMPACT ON STUDENTS’ VOCABULARY AND ATTITUDE - Yossi Rahmawati; Khoirul Anwar (IKIP Siliwangi, 2022)
TikTok has become one of the most popular social media platforms for sharing short videos. Many relevant studies have suggested that social media integrated with short videos can help increase their mastery of English. Therefore, this study aims to know whether the TikTok application can improve students’ vocabulary and investigate their attitude towards learning English through the TikTok application. The researcher employed quantitative approaches in this study, including a one-group pretest-posttest design and a semi-structured interview as a measuring instrument. The subject of this study was sixth-grade students of Phanang-Phakerng School Thailand. The result showed that the improvement percentage was 95%, which means that the TikTok application effectively affects students’ learning outcomes in mastering vocabulary. Based on the interview results, the participants showed positive attitudes toward learning English through the TikTok application. Therefore, this result of this study could give an alternative strategy to the teacher to teach vocabulary by using the TikTok application in the classroom due to the students' positive attitudes. Keywords: TikTok, Vocabulary, Students’ Attitude